Susceptibility testing of clinical isolates of Enterococcus faecium and Enterococcus faecalis. - Louie, M (1992)
We collected 103 clinical Enterococcus faecium isolates from across Canada, performed standard broth microdilution susceptibility testing, and compared these results with results from the MicroScan Pos MIC Type 6 panel (Baxter Health Care Corp., West Sacramento, Calif.) and the AMS-Vitek Gram-Positive Susceptibility card (Vitek Inc., St. Louis, Mo.). High-level aminoglycoside resistance to gentamicin and streptomycin was detected by a single-concentration agar method with 1,000 micrograms of each aminoglycoside per ml. In addition, we tested the effect of the lower calcium content in broth media as recommended in National Committee for Clinical Laboratory Standards (NCCLS) guideline M7-A2 on the activity of the highly calcium-dependent agent daptomycin. Of the 103 E. faecium isolates, there were 4 and 30 isolates with high-level gentamicin resistance (HLGR) and high-level streptomycin resistance (HLSR), respectively. An additional 39 (37 with HLGR and 36 with HLSR) E. faecium isolates were tested by both the MicroScan and the AMS-Vitek systems. The AMS-Vitek card demonstrated sensitivities of 95 and 82% for detecting HLGR strains and HLSR strains, respectively. The MicroScan panel demonstrated improved sensitivities for detecting HLGR (42 to 97%) and HLSR (64 to 84%) when readings were performed manually instead of being generated automatically. Ampicillin resistance (MIC, greater than or equal to 16 micrograms/ml) was detected in 23 of the 103 E. faecium isolates. Only 14 and 20 of these were detected by the MicroScan panels and AMS-Vitek cards, respectively. beta-Lactamase activity was not detected in any isolates. The lower calcium content in broth media recommended by NCCLS guideline M7-A2 markedly reduced the in vitro activity of daptomycin against Enterococcus spp.